(untitled) (Research, Society and Development, 2023)
The summary urine test consists of physical-chemical analysis and sedimentoscopy. When the physical-chemical phase is normal, it is discussed not carrying out the sedimentoscopy step. This study aimed to evaluate the importance of normal physicochemical results of urine as a screening test for sedimentoscopy. The results of 3661 routine urine summary tests (medium jet) performed at the Clementino Fraga Laboratory, Fortaleza-Ceará, in January 2018 were analyzed. The collected data were recorded, tabulated and analyzed in the SPSS software version 17.0. It was observed that 77.92% of the urine tests showed no physical-chemical alterations. Of the 2658 urines with normal physicochemical analyses, 87.06% had normal sedimentoscopies within a confidence interval of 85.78% - 88.34%. Analyzing the negative predictive value (NPV) of urine with normal physicochemical and correlating it with the alterations found in the sedimentoscopies, we verified that this method has 99.8% of accuracy for all the elements found. The absence of leukocyte esterase and red blood cells in the physical-chemical analysis has an accuracy for sedimentoscopy of 97.5% and 98.2%, respectively. The present study suggests the use of normal physicochemical analysis as an exclusion factor for sedimentoscopy.